Growth of Wheat (Triticumaestivum L.) under Raised Bed Planting Method in Rice-Wheat Cropping System (Bangladesh Rice Journal, 2016)
CORRECTION: Due to a number of formatting and layout issues, the PDF of this paper was replaced on 10th October 2016. The page numbers of this article have changed from 45-54 to 47-56.An experiment was conducted at the Bangladesh Rice Research Institute, Gazipur during Rabi season 2001-02 and 2002-03 (November to March) to evaluate the effect of raised bed planting method on different crop growth parameters, which influence the wheat productivity. Total tiller production, leaf area index (LAI), dry mater production (DMP), crop growth rate (CGR) and agronomic productivity of wheat under bed planting on 70, 80 and 90 cm wide beds with two and three plant rows bed-1 and conventional method were investigated. The number of tillers m-2 in 70 cm beds with both two and three rows were statistically identical to conventional method. Wheat plants grown on narrow beds (70 cm) produced similar LAI to that grown in conventional method but plants in wider beds (80 and 90 cm) had less LAI than that in conventional method. Similarly, DMP and CGR in 70 cm beds were either comparable or higher than conventional method. Grain yield of 70 cm beds were higher than conventional method. Wheat in 70 cm beds increased number of panicles m-2, number of grains panicle-1 and 1000-grain weight of wheat.Bangladesh Rice j. 2015, 19(2): 47-56